Cochlear implantation in patients deafened by ototoxic drugs. (1st September 2013) - Nichani, Jaya; Bruce, Iain A; Mawman, Deborah; Khwaja, Sadie; Ramsden, Richard; Green, Kevin
Abstract : Objective To investigate the outcome of cochlear implantation (CI) in patients deafened by ototoxic drugs and to compare this, with the outcome of CI in sudden sensorineural hearing loss (SSNHL) with a similar duration of deafness. Methods The Manchester Auditory Implant Centre database was reviewed to identify patients who were implanted to rehabilitate profound sensorineural hearing loss resulting from treatment with ototoxic agents and patients with SSNHL group. A retrospective case note review of selected patients was carried out. Primary outcome measure was post-implantation Bamford-Kowal-Bench (BKB) score in quiet in both the groups. Secondary outcome measure was any significant complications following implantation. Results We identified 14 patients in the ototoxic group, which were matched with 13 patients in the SSNHL group. The post-operative BKB score in the ototoxic group ranged from 33 to 100% (median score 91%). One patient had bilateral CI. One patient required explantation following an infection. The post-operative BKB score in the SSNHL group ranged from 16 to 100% (median score 88%). One patient in this group could not be tested using this method as they did not have open set speech discrimination. Two patients in this group had bilateral CI. The data were analysed using Mann-Whitney U test. There was no statistically significant difference in the BKB scores in the two groups of patients ( P value −0.983). Conclusion Patients with profound hearing loss secondary to ototoxic agents can be rehabilitated successfully with CI. The outcomes may be variable and may be dependent on the underlying pathology for which the ototoxic agents were prescribed.